Enhancement of the Up-conversion Luminescence of 12CaO · 7Al2O3:Tm3+/Yb3+ Doped with Alkaline Earth Metal Ions. (2nd September 2018) - Xu, Yanling; Zhao, Zhenni; Wang, Rui; Li, Yuemei; Zheng, Wei; Zhang, Zhirong
ABSTRACT: 12CaO · 7Al2 O3 doped with lanthanide is characterized by remarkable and technologically important up-conversion emission. However, the low up-conversion efficiency still remains the main limitation for practical applications. To improve the efficiency, bivalent alkaline earth ions (Mg 2+, Sr 2+, Ba 2+ )-tridoped Tm 3+ /Yb 3+ /12CaO · 7Al2 O3 were synthesized through a high-temperature solid-state reaction. The up-conversion luminescence properties of the samples were investigated by X-ray diffraction, fluorescence spectral measurement pump power, and fluorescence decay curves. The luminescence intensity of samples was significantly enhanced by bivalent alkaline earth ions. 12CaO · 7Al2 O3 doped with Sr 2+ ions has stronger effects on up-conversion enhancement, which is better than Mg 2+ and Ba 2+ . The up-conversion emission intensity was enhanced by 318 times and the red emission intensity by 218 times with 10 mol% Sr 2+ ion. Additionally, the blue and red up-conversion emission peaks at 475 and 650 nm corresponding to energy transitions of 1 G4 → 3 H6 and 1 G4 → 3 F4, 3 F2 → 3 H6 were characterized using steady-state rate equations.